2007
DOI: 10.1210/jc.2006-0852
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Hormone Therapy on Serum Adiponectin and Resistin Levels in Short, Small-for-Gestational-Age Children and Associations with Cardiovascular Risk Parameters

Abstract: Compared with normal-statured controls, short prepubertal SGA children had similar adiponectin and lower resistin levels. Two years of GH treatment had no effect on their adiponectin and resistin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…This discrepancy with the results documented by other authors (25,26,27) may lie in the fact that most studies evaluate heterogeneous groups of SGA children with different BMI. Instead, our results agree with a recent study of Willemsen et al 28 , showing normal adiponectin levels in children born SGA that remain short, who are in general at a lower risk for overweight during the early years of life. The lack of correlation between adiponectin and insulin sensitivity parameters in our population might be due to the low BMI exhibited by the children, even those with catch up growth.…”
Section: Discussionsupporting
confidence: 92%
“…This discrepancy with the results documented by other authors (25,26,27) may lie in the fact that most studies evaluate heterogeneous groups of SGA children with different BMI. Instead, our results agree with a recent study of Willemsen et al 28 , showing normal adiponectin levels in children born SGA that remain short, who are in general at a lower risk for overweight during the early years of life. The lack of correlation between adiponectin and insulin sensitivity parameters in our population might be due to the low BMI exhibited by the children, even those with catch up growth.…”
Section: Discussionsupporting
confidence: 92%
“…Chen et al reported IGF-1 decreases resistin gene expression and protein secretion in vitro [18]. Willemsen et al performed a 2-year study with infants having low birth weight and short stature according to gestational age [19]. During this period they determined resistin levels in children having high IGF-1 levels and taking GH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a mouse model, the adiponectin levels were negatively correlated with GH, and a role for adiponectin in GH-induced insulin resistance was suggested [40]. However, in another study of SGA children, no association between adiponectin and insulin was found [41]. The last finding is in line with the lack of correlation between the adiponectin levels and fasting insulin levels at any time point in our study for the whole group, as well as for the subgroups AGA/SGA and GHD/ISS.…”
Section: Discussionmentioning
confidence: 99%